THE IMPLEMENTATION OF SALES PROMOTION AND EASE OF PAYMENT METHODS FOOD AND BEVERAGE BUSINESSES IN PARAPAT TOURIST AREA ON CUSTOMER REVISIT INTEREST - Syahrul Syahrul; Riana Handayani Silalahi; Sepdwiyana Donargo (RADJA PUBLIKA, 2026)
This study aims to analyze the impacts of sales promotion, payment methods, and the simultaneous effect of both sales promotion and payment methods on customer revisit intention in the food and beverage business in Parapat. The data analysis used in this research is quantitative analysis, processed using the Statistical Package for the Social Sciences (SPSS). This type of research is associative or causal, aiming to determine the relationship or influence of sales promotion and the ease of payment methods on customer revisit intention. The results show that the t-value of 5.783, which is greater than the t-table value of 1.984, with a correlation value of 0.869. This indicates that sales promotion has a positive and significant influence, categorized as